APPLICATION OF ARTIFICIAL INTELLIGENCE IN MECHATRONIC SYSTEMS - A.P. Sobchak (National Technical University "Kharkiv Polytechnic Institute", 2013)
This article discusses the main issues of artificial intelligence and its implementation in daily life in the form of control systems for mechatronic systems. Due to intensive application of the latest scientific and technological achievements and a new element base, there spring up new technologies of artificial intelligence creation principles and laws realization, examples of which given in the article